Multisite Study of Evoked Potentials in Rett Syndrome. Issue 4 (4th February 2021) - Saby, Joni N.; Benke, Timothy A.; Peters, Sarika U.; Standridge, Shannon M.; Matsuzaki, Junko; Cutri‐French, Clare; Swanson, Lindsay C.; Lieberman, David N.; Key, Alexandra P.; Percy, Alan K.; Neul, Jeffrey L.; Nelson, Charles A.; et al.
Abstract : Objective: The aim of the current study was to evaluate the utility of evoked potentials as a biomarker of cortical function in Rett syndrome (RTT). As a number of disease‐modifying therapeutics are currently under development, there is a pressing need for biomarkers to objectively and precisely assess the effectiveness of these treatments. Method: Yearly visual evoked potentials (VEPs) and auditory evoked potentials (AEPs) were acquired from individuals with RTT, aged 2 to 37 years, and control participants across 5 sites as part of the Rett Syndrome and Related Disorders Natural History Study. Baseline and year 1 data, when available, were analyzed and the repeatability of the results was tested. Two syndrome‐specific measures from the Natural History Study were used for evaluating the clinical relevance of the VEP and AEP parameters. Results: At the baseline study, group level comparisons revealed reduced VEP and AEP amplitude in RTT compared to control participants. Further analyses within the RTT group indicated that this reduction was associated with RTT‐related symptoms, with greater severity associated with lower VEP and AEP amplitude. In participants with RTT, VEP and AEP amplitude was also negatively associated with age. Year 1 follow‐up data analyses yielded similar findings and evidence of repeatability of EPs at the individual level. Interpretation: The present findings indicate the promise of evoked potentials (EPs) as an objective measure of disease severity in individuals with RTT. Our multisite approach demonstrates potential research and clinical applications to provide unbiased assessment of disease staging, prognosis, and response to therapy. ANN NEUROL 2021;89:790–802